2020
DOI: 10.2196/18528
|View full text |Cite|
|
Sign up to set email alerts
|

Using Serious Games for Antismoking Health Campaigns: Experimental Study

Abstract: Background Serious games for health have been gaining in popularity among scholars and practitioners. However, there remain a few questions to be addressed. Objective This study tests the effects of a serious game and fear appeals on smoking-related outcomes. More specifically, this research aims to understand how serious games function as a more effective vehicle for a health campaign than a traditional medium, such as a print-based pamphlet. Further, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…Learning is achieved through the chosen mechanics and rules that drive the processes in the game. The anatomy of the game will have maximum procedural rhetoric with this approach [50,51], which makes it appropriate to experience the perspective of another and, by reproducing feelings, makes clear what it means to lose autonomy through unsolicited help.…”
Section: Serious Games For Perspective Takingmentioning
confidence: 99%
“…Learning is achieved through the chosen mechanics and rules that drive the processes in the game. The anatomy of the game will have maximum procedural rhetoric with this approach [50,51], which makes it appropriate to experience the perspective of another and, by reproducing feelings, makes clear what it means to lose autonomy through unsolicited help.…”
Section: Serious Games For Perspective Takingmentioning
confidence: 99%
“…Adolescents, especially, tend to have excellent adaptability to new technologies and possess substantial knowledge and experience with games as compared to users of other age groups [36]. Given the research on adolescents' engagement with videogames [37] and studies conducted in game-based learning [38] and narrative persuasion [39][40][41], one may anticipate the positive influence of serious games on adolescents' learning and persuasion outcomes. When it comes to cancer prevention, adolescents can learn about complex cancer concepts and relevant prevention and treatment methods by interacting with engaging characters and objects and actively performing game quests embedded in serious games [34].…”
Section: Serious Games In the Context Of Cancer Control In Children A...mentioning
confidence: 99%
“…The study by Panic et al [ 24 ] on children suggested that the interactive game used for the appeal distracted participants, thereby preventing the processing of the appeal content. In contrast, Kim et al [ 25 ] found that a game-based fear appeal resulted in stronger intentions to quit adverse behavior than a brochure. However, it has to be noted that these findings are hard to ground in assumptions of interaction alone, as the difference in the format of the appeal introduces more differences between conditions than interaction alone.…”
Section: Introductionmentioning
confidence: 98%